5-Aminolevulinic Acid-Induced Fluorescence in Focal Cortical Dysplasia: Report of 3 Cases. Issue 4 (16th June 2018) - Roberts, David W; Bravo, Jaime J; Olson, Jonathan D; Hickey, William F; Harris, Brent T; Nguyen, Lananh N; Hong, Jennifer; Evans, Linton T; Fan, Xiaoyao; Wirth, Dennis; Wilson, Brian C; Paulsen, Keith D
Abstract: BACKGROUND: Three patients enrolled in a clinical trial of 5-aminolevulinic-acid (5-ALA)-induced fluorescence-guidance, which has been demonstrated to facilitate intracranial tumor resection, were found on neuropathological examination to have focal cortical dysplasia (FCD). OBJECTIVE: To evaluate in this case series visible fluorescence and quantitative levels of protoporphyrin IX (PpIX) during surgery and correlate these findings with preoperative magnetic resonance imaging (MRI) and histopathology. METHODS: Patients were administered 5-ALA (20 mg/kg) approximately 3 h prior to surgery and underwent image-guided, microsurgical resection of their MRI- and electrophysiologically identified lesions. Intraoperative visible fluorescence was evaluated using an operating microscope adapted with a commercially available blue light module. Quantitative PpIX levels were assessed using a handheld fiber-optic probe and a wide-field imaging spectrometer. Sites of fluorescence measurements were co-registered with both preoperative MRI and histopathological analysis. RESULTS: Three patients with a pathologically confirmed diagnosis of FCD (Types 1b, 2a, and 2b) underwent surgery. All patients demonstrated some degree of visible fluorescence (faint or moderate), and all patients had quantitatively elevated concentrations of PpIX. No evidence of neoplasia was identified on histopathology, and in 1 patient, the highest concentrations of PpIX were found at a tissue site with marked gliosis but no typical histological features of FCD. CONCLUSION: FCD has been found to be associated with intraoperative 5-ALA-induced visible fluorescence and quantitatively confirmed elevated concentrations of the fluorophore PpIX in 3 patients. This finding suggests that there may be a role for fluorescence-guidance during surgical intervention for epilepsy-associated FCD.